Video Stimulated Recall in Indonesian Language Teacher Education: A Lesson of Pre-Service Teachers’ Professional Identity Construction - Eriyani, Reni Nur; Murtadho, Fathiaty; Boeriswati, Endry; Sulistyaningrum, Siti Drivoka (Journal of Language and Literature Studies, 2026)
Reflective practice is essential for fostering professional growth in teacher education, and video-stimulated recall (VSR) has emerged as a powerful tool to support this process. However, the application of VSR in the Indonesian context, particularly for Indonesian language pre-service teachers, remains underexplored. This study departs from the gap between the significant potential of the Video Stimulated Recall (VSR) technique in teacher professional development and the minimal exploration of this method for Indonesian language pre-service teachers, particularly within the context of the Teacher Professional Education Program (PPG). The purpose of this study is to explore and analyze how self-narratives about professionalism are constructed and transformed by Indonesian language pre-service teachers through the VSR process on their teaching practices. This research employs a qualitative approach with a narrative study design. Six Indonesian language pre-service teachers participated in three VSR cycles consisting of planning, lesson implementation, video recording, and video-stimulated reflection using a reflection journal based on Farrell's framework. Data were also collected through semi-structured interviews and analyzed using thematic analysis. The main findings indicate that VSR reveals genealogical narratives where participants' teaching practices are influenced by past experiences; a dynamic negotiation occurs between ideal principles and classroom realities; VSR bridges the theory-practice gap; a tangible transformation across cycles is observed in the form of increased self-confidence, mastery of content, and sensitivity to students; and VSR encourages the integration of moral values, social sensitivity, and life skills into learning. This study concludes that VSR with Farrell's reflective framework is a powerful approach for building the professional self-narrative of Indonesian language pre-service teachers. Implications suggest that PPG programs are recommended to integrate VSR as a routine activity to foster sustainable reflective awareness.